Peran Intelektual Indonesia dalam Politik pada Periode 1997-1999 - Irwan Luigi Mukhtar Pakpahan; Pulung Sumantri; Nurasiah Nurasiah (Medan Resource Center, 2024)
This research delves into the intricate dynamics of Indonesian intellectuals and the political landscape from 1997 to 1999. Utilizing qualitative research and literature analysis, it unveils the pivotal role intellectuals played in shaping democracy in Indonesia during these tumultuous years. The findings emphasize democracy's imperative nature, evolving from a necessity to a social reality. Intellectuals' engagement from 1997-1999 reflects a collective effort to establish a democratic framework. The social and political dynamics of the 1998 reform era significantly influenced democratic development. Presently, the impact is evident, granting unprecedented freedom of expression, association, and press freedom. The Reform Movement, responding to multifaceted crises, emerged as an unwavering force, enjoying overwhelming public support. This research illuminates the Reform Movement's profound significance in shaping Indonesia's democratic landscape, underscoring its nonnegotiable essence.